Zigzag and Helical AlN Layer Prepared by Glancing Angle Deposition and Its Application as a Buffer Layer in a GaN-Based Light-Emitting Diode. (2nd October 2012) - Chen, Lung-Chien; Tien, Ching-Ho; Xuguang, Liu; Bingshe, Xu
Abstract : This study investigates an aluminum nitride (AlN) nanorod structure sputtered by glancing angle deposition (GLAD) and its application as a buffer layer for GaN-based light-emitting diodes (LEDs) that are fabricated on sapphire substrates. The ray tracing method is adopted with a three-dimensional model in TracePro software. Simulation results indicate that the zigzag AlN nanorod structure is an optimal buffer layer in a GaN-based LED. Furthermore, the light output power of a GaN-based LED with a zigzag AlN nanorod structure improves to as much as 28.6% at a forward current of 20 mA over that of the GaN-based LED with a normal AlN buffer layer.